2017
DOI: 10.1038/srep43633
|View full text |Cite
|
Sign up to set email alerts
|

Association between functional polymorphisms in the promoter of the miR-143/145 cluster and risk of intracranial aneurysm

Abstract: MicroRNAs (miRs)-143/145 are involved in various biological processes related to aneurysm formation and are downregulated in patients with intracranial aneurysm (IA). We aimed to determine whether two functional polymorphisms (i.e. rs4705342 and rs4705343) in the promoter of miR-143/145 are related to IA risk. A case-control study was undertaken to examine the association of rs4705342 and rs4705343 with IA risk, including 565 patients with IA and 622 age- and gender-matched controls. rs4705342 was analysed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Moreover, a clinical study has presented that the miR-143/145 cluster of IA patients is downregulated compared to healthy subjects [11]. In addition, it is previously discussed that miR-143/145 takes part in various biological processes associated with aneurysm formation and is downregulated in patients with IA [20]. All these findings are more or less echoed with the previous exploration outcomes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, a clinical study has presented that the miR-143/145 cluster of IA patients is downregulated compared to healthy subjects [11]. In addition, it is previously discussed that miR-143/145 takes part in various biological processes associated with aneurysm formation and is downregulated in patients with IA [20]. All these findings are more or less echoed with the previous exploration outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study has demonstrated the involvements of lncRNA-related competitive endogenous RNA networks in IA [19]. Also, a recent study has provided a proof that functional polymorphism in miR-143/145 gene promoter region is connected with the risk of IA [20]. In a study conducted by Xu et al, it is shown that overexpression of angiogenic factors, such as VEGFA, may be related to IA formation and rupture [21].…”
Section: Discussionmentioning
confidence: 97%
“…Since miR-143 and miR-145 are among the most commonly downregulated miRNAs in neoplasms such as gastric, urinary bladder, colorectal cancer, as well as PCa, genetic variants potentially affecting the expression of their precursor have been investigated in multiple malignant diseases. Among a number of SNPs located within the potential regulatory region of miR-143/145 cluster, the effect on transcriptional actions was revealed for rs4705343 and rs4705342 (Wei et al, 2016[ 35 ], Sima et al, 2017[ 32 ]). Also, a previous report suggests the association of genetic variant rs4705342 with PCa (Chu et al, 2016[ 7 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Local mass effects may contribute to local neurological deficits depending on adjacent neural structures or bone anatomy. These lesions may also rupture, leading to subdural hematomas or hemorrhage (Sima, Sun, & Zhou, ). In this paper, we investigated the association between elongator protein complex 4 ( ELP4 ) rs986527 polymorphism and the occurrence and development of intracranial arachnoid cysts.…”
Section: Introductionmentioning
confidence: 99%